Developing classroom-based language assessment literacy for in-service EFL teachers: The gaps. (June 2019) - Lan, Chunshou; Fan, Shengyu
Highlights: On average, EFL teachers investigated are at the level of functional literacy. EFL teachers lack relevant theories in evaluating the quality of assessments. EFL teachers underdeveloped particularly in technical skills and language pedagogy. EFL teachers expect to be procedurally and conceptually literate in CBLAL by training. Technical skills and language pedagogy are the priority for professional training. Abstract: Teachers are expected to keep up to date with challenges and expectations that arise in classroom-based language assessment. This study responds to the call for increased research in the area of language assessment literacy in the context of classroom-based assessment. In particular, our research provides insights into assessment literacy training for in-service teachers of English as a foreign language (EFL). By way of gap analysis based on a questionnaire of 344 EFL teachers in Chinese middle schools, this study found that EFL teachers investigated were nearly at the functional level of classroom-based language assessment literacy (CBLAL), and that they wished to be procedurally and conceptually literate through professional training so as to understand the central concepts of classroom-based language assessment and use their knowledge in practice. The study will shed light on views regarding the assessment literacy topics that are important to be included in in-service EFL teacher training programs.